Clinical Presentation of Patients With Tension Pneumothorax: A Systematic Review. Issue 6 (June 2015) - Roberts, Derek J.; Leigh-Smith, Simon; Faris, Peter D.; Blackmore, Christopher; Ball, Chad G.; Robertson, Helen Lee; Dixon, Elijah; James, Matthew T.; Kirkpatrick, Andrew W.; Kortbeek, John B.; Stelfox, Henry T.
Abstract : Objective: To determine whether the reported clinical presentation of tension pneumothorax differs between patients who are breathing unassisted versus receiving assisted ventilation. Background: Animal studies suggest that the pathophysiology and physical signs of tension pneumothorax differ by subject ventilatory status. Methods: We searched electronic databases through to October 15, 2013 for observational studies and case reports/series reporting clinical manifestations of tension pneumothorax. Two physicians independently extracted clinical manifestations reported at diagnosis. Results: We identified 5 cohort studies (n = 310 patients) and 156 case series/reports of 183 cases of tension pneumothorax (n = 86 breathing unassisted, n = 97 receiving assisted ventilation). Hypoxia was reported among 43 (50.0%) cases of tension pneumothorax who were breathing unassisted versus 89 (91.8%) receiving assisted ventilation ( P < 0.001). Pulmonary dysfunction progressed to respiratory arrest in 9.3% of cases breathing unassisted. As compared to cases who were breathing unassisted, the adjusted odds of hypotension and cardiac arrest were 12.6 (95% confidence interval, 5.8–27.5) and 17.7 (95% confidence interval, 4.0–78.4) times higher among cases receiving assisted ventilation. One cohort study reported that none of the patients with tension pneumothorax who were breathing unassisted versus 39.6% of those receiving assisted ventilation presented without an arterial pulse. In contrast to cases breathing unassisted, the majority (70.4%) of those receiving assisted ventilation who experienced hypotension or cardiac arrest developed these signs within minutes of clinical presentation. Discussion: The reported clinical presentation of tension pneumothorax depends on the ventilatory status of the patient. This may have implications for improving the diagnosis and treatment of this life-threatening disorder. Abstract : Supplemental Digital Content is Available in the Text.This systematic review suggests that patients with tension pneumothorax who are breathing unassisted frequently present with predominantly respiratory signs and symptoms whereas those receiving assisted ventilation most often present with hypoxemia, hypotension, and/or cardiac arrest. This may have implications for improving the diagnosis and treatment of this life-threatening disorder.